Kolaborasi Interfungsional dan Kualitas Pelayanan Pusat Kontrol Operasi di Bandara I Gusti Ngurah Rai - Reynold, Binsar; Sodikin, Alit; Marina, Sandriana; Rafi, Salahudin; Perwitasari, Erni Pratiwi; Pahala, Yosi (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2023)
The study aims to analyze the Airport Operation Control Center (AOCC) operational performance through interfunctional cooperation on the operational quality of I Gusti Ngurah Rai Airport in Bali. The airport facilities and infrastructures are considered inadequate when they are compared to the growth rate of air traffic. Ideally, the study wants to find out the effect of Airport Operation Control Center’s performance on airport operational service quality and the mediating role of interfunctional cooperation on airport operational service quality. The sample of 49 stakeholders and AOCC users at I Gusti Ngurah Rai Airport in Bali was used as the saturated sampling method and the data were analyzed using Structural Equation Model (SEM) with Smart PLS program. The results show that the operational performance has direct effect on interfunctional cooperation and airport operational service quality. Furthermore, the interfunctional cooperation is able to mediate the AOCC operational performance and the quality of airport operational services.